Screening Upland Varieties of NERICA and its Parents for Resistance to Stalk-eyed Fly, Diopsis sp. (Diptera, Diopsidae) in Benin - Togola, A.; Nwilene, F.E.; Agbaka, A.; Degila, F.; Tolulope, A.; Chougourou, D. (Science Alert, 2010)
The stalk-eyed fly or Diopsid, Diopsis sp. (Diptera, Diopsidae) is an economically significant insect pest of rice in Tropical Africa. The objective of this study is to develop a fast screening method of rice varieties for resistance to Diopsis sp. in a view to advice breeders on resistance sources and to guide producers in the use of resistant varieties to reduce or avoid insecticidal treatments of the fields. The study was conducted in 2008 at the AfricaRice/IITA Station, Cotonou where, 18 upland NERICA varieties and their parents (Oryza glaberrima and O. sativa) were twice screened under artificial infestation of Diopsid’s eggs and adults. The screening method was based on Brown Plant Hopper screening techniques using small cages. As results, only NERICA16 and NERICA18 showed good resistance to Diopsid attack at 20 Days after Infestation (DAI) under egg infestation. The remaining 18 entries were more or less susceptible. Under adult infestation, 16 NERICA varieties showed very good resistance to the stalk-eyed fly attack at 20 DAI. Of these, NERICA18, NERICA11, NERICA6 and NERICA15 were highly resistant (% deadhearts <7%). Only NERICA9 and NERICA17 were moderately susceptible. The African O. glaberrima parent CG14 was the most resistant entry. The Asian parent line WAB56-104 also suffered less damage from Diopsis sp. than most of the NERICAs. In this experiment, the adult infestation appeared to be more realistic than infestation with eggs because it is a free choice method in which pest pressure is weak and where varieties can demonstrate their real behaviour.